Amitiés particulières au Maghreb : sociabilités et discours homosexuels - Valérie Beaumont (L’Année du Maghreb)
This article describes a number of cases of male homosexuality in the Maghreb. We will examine the construction of identities in individuals with exclusively homosexual orientation, as well as bisexuality existing in more traditional social settings. In a region still immersed in homosensuality, we will try to point out the contrast between the new sexual practices and the discourse produced about them. We will explain why, in the course of ethnographic research on sexual practices in Maghreb, any attempt to confine relations between males to a typology that isolates friendship, love and sexual desires would be inappropriate. Finally, this article reveals the means used to objectify identities and sexual orientations, particularly through migration, associations and the Internet, in a context where social and ideological currents, whether local or external, are structuring new patterns of life that lead to both openness and withdrawal back to conservative moral and religious values.